2017
DOI: 10.1177/0963662517690293
|View full text |Cite
|
Sign up to set email alerts
|

‘I have faith in science and in God’: Common sense, cognitive polyphasia and attitudes to science in Nigeria

Abstract: This study, of modern common sense in Nigeria, combines questionnaires and interviews to examine the compatibility and incompatibility of religion and science. Nigeria is a large country with a complex diversity of religious, ethnic and cultural practices that condition the reception and elaboration of science in everyday life. We find evaluative attitudes to science structured as ‘progress’, ‘fear’ and ‘mythical image’. Scientific knowledge and religiosity have a direct bearing on expectations of progress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
0
37
0
2
Order By: Relevance
“…For example, exposure to anti-vaccine CTs decreases people’s intentions to vaccinate ( Jolley and Douglas, 2014a ). Similar society-wide public health implications arose for polio vaccination in Nigeria ( Falade and Bauer, 2017 ), where the vaccine was seen as the instrument of a Western birth-control plot. In the United States, belief that birth control and HIV/AIDS are forms of genocide against African Americans is associated with negative attitudes toward contraception ( Bogart and Thorburn, 2006 ).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, exposure to anti-vaccine CTs decreases people’s intentions to vaccinate ( Jolley and Douglas, 2014a ). Similar society-wide public health implications arose for polio vaccination in Nigeria ( Falade and Bauer, 2017 ), where the vaccine was seen as the instrument of a Western birth-control plot. In the United States, belief that birth control and HIV/AIDS are forms of genocide against African Americans is associated with negative attitudes toward contraception ( Bogart and Thorburn, 2006 ).…”
Section: Introductionmentioning
confidence: 83%
“…Contradictions between CTs may not be detected or experienced as contradictions by believers, because the representations of the CTs do not have precise interpretations, and so do not support a sharp sense of conflict. They may thus permit coexistence of apparently contradictory knowledge systems ( Legare and Gelman, 2008 ) or cognitive polyphasia ( Jovchelovitch, 2006 ; Falade and Bauer, 2017 ), in which aspects of conventional and conspiratorial worldviews offer complementary, rather than competing explanations of destabilizing events.…”
Section: Discussionmentioning
confidence: 99%
“…The move from conceptual conflicts focused on theology and belief has also inspired scholars to push for studying ordinary religious people’s religious attitudes, views, and behaviors, instead of constantly focusing on religious leaders and elites (Evans, 2011, Evans & Evans 2008; Falade & Bauer, 2018). By focusing on everyday attitudes and behaviors, scholars have documented how science and medicine are embraced selectively, especially in cases when they can mirror and bolster communal norms.…”
Section: Covid-19 Religion and Ethnic Minoritiesmentioning
confidence: 99%
“…He found that issues other than the epistemological relationship between science and religion were at the core of the debate, including the relationship between religion and the state, the nature of science education in schools, school performance, and the role of private companies in education. Based on interview and questionnaire research, Falade and Bauer () found complexity in the relationship between science and religion for publics in Nigeria as well.…”
Section: Understanding Science and Accepting Sciencementioning
confidence: 99%